Polyclonal Immunotactoid Glomerulopathy Associated with Monoclonal Gammopathy of IgM Type and Underlying Plasmacellular Disease: Successful Treatment with Rituximab Alone - Wolfgang Neukirchen; Anne Oesterling; Dirk Oliver Wennmann; Barbara Heitplatz; Peter Ritter; Hartmut Merz; Veit Busch (Case Reports in Nephrology and Dialysis, 2022)
Immunotactoid glomerulopathy (ITG) occurs infrequently and is characterized by organized IgG containing deposits. It most usually manifests as a concomitant disease of a broad spectrum of oncologic entities. We here present an exceptional case of ITG without glomerular light chain restriction secondary to a IgM kappa type monoclonal gammopathy of undetermined significance. Due to nephrotic syndrome and deterioration of kidney function a rituximab monotherapy was initiated without targeting the plasmacellular augmentation, which was confirmed as the underlying process. The treatment led to a long-term improvement of proteinuria and stabilization of glomerular filtration rate. Its therapeutic effect has to be attributed to immunomodulatory capacities and targeting of podocytes rather than to be interpreted as directed against a bone marrow or glomerular clone. We conclude that rituximab therapy may be a valuable part of the therapeutic options in ITG irrespective of the underlying oncologic entity.